Enriched semantic markup for postgraduate programs in Latin America - Roa-Martínez, Sandra Milena [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio; Pastor-Sánchez, Juan Antonio (FapUNIFESP (SciELO), 2018)
Enriched semantic markup provides meaning to content and allows interoperability between machines, encouraging the visualization of information for users, such as the use of rich snippets, which expand the information provided by search engines. The objective was to analyze and enrich semantically the contents of the graduate programs delivered to the users, so that they are interoperable and contribute to the community through the reuse and proposal of extension of a new entity. The methodology used was descriptive based on the compilation and systematization of qualitative and quantitative information, analysis and characterization of the contents that currently contain the studied web pages and the Schema.org vocabulary. As result, a content semantically enriched markup proposal is presented for the postgraduate programs offered by some Latin American universities contained in a new entity named ProgramaPosgrado, based on the vocabulary of Schema.org. It was concluded that enriched semantic markup using rich snippets is a true Semantic Web application that adds visibility and interoperability to Web content, verifying that Schema.org is a vocabulary that can be extended for use in different fields.
Marcado semántico enriquecido para programas de posgrado en Latinoamérica
Keywords: Postgraduate; Rich snippets; Schema.org; Semantic markup